Depression Has an Adverse Effect on Diabetes Treatment and Outcomes - Buckley, Rita (MD Conference Express, 2011)
Comorbid depression in diabetes is highly prevalent and has a negative impact on well-being and diabetes control [van der Feltz-Cornelis CM et al. Gen Hosp Psychiatry 2010]. Diabetes patients with comorbid depression are less likely to engage in physical activity, comply with dietary advice, and stop smoking [DiMatteo MR et al. Arch Intern Med 2000].